Heart Transplantation and End-Stage Cardiac Amyloidosis: A Review and Approach to Evaluation and Management - Estep, Jerry D. (The Methodist Hospital, Houston, Texas, 2012)
Cardiac amyloidosis is one of the most common of the infiltrative cardiomyopathies and is associated with a poor prognosis. The extent of cardiac involvement with amyloid deposition is an important determinant of treatment options and is the major determinant of outcome in patients with amyloidosis. Several small case series with sequential orthotopic heart transplantation and autologous stem cell transplant have demonstrated an improvement in post-transplant outcome and have revived enthusiasm about heart transplantation for patients with end-stage heart failure due to AL amyloidosis. The purpose of this review is to summarize the evaluation and management of cardiac amyloidosis and to provide our single-center experience with end-stage heart failure due to AL amyloidosis treated with heart transplantation followed by an autologous stem cell transplant.